Company Growth, Company Size, Capital Structure and Profitability on Company Value in IDX-Listed Manufacturing Companies - Sahputra, Rian; Saputra, Mulia; Maryasih, Lilis (Devotion : Journal of Research and Community Service, 2024)
This study aims to examine the effect of company growth, company size (SIZE), capital structure, (DER), and profitability (ROE) on company value (PBV) in manufacturing companies listed on the Indonesia Stock Exchange. The sample consisted of 194 companies, with 49 selected using purposive sampling techniques. The study used multiple linear regression analysis and company financial statement data from 2018-2020. The coefficient of determination function is to measure how much influence between Company Growth, Company Size, Capital Structure, and Profitability on Company Value. The results of statistical testing show that the company's growth partially affects the value of the company. The size of a large or small company will not be able to affect its value. It also shows that if the company increasingly uses long-term debt to finance its assets, it can increase the value.